Desenvolvimento de um conversor monofásico assimétrico com capacitores flutuantes - Saccol, Gabriel Avila (2019)
This work presents a comprehensive analysis of a single-phase full-bridge asymmetrical flying capacitor multilevel converter. Multilevel converters are a promising alternative to high power applications, since they use low voltage semiconductors to produce output waveforms with an increased number of levels. Among the conventional topologies, the flying capacitor converter has redundant states, which can be used for the voltage balance of the capacitors. Furthermore, the number of output voltage levels can be extended by using different voltage levels for flying capacitors, reducing or even eliminating the output filter. In this work, a methodology for the determination of the flying capacitor voltages is proposed to synthesize equally spaced output voltage levels for a full-bridge asymmetrical flying capacitor converter. A detailed analysis of the flying capacitor voltages balance is also performed, through the space vector modulation. Finally, a nine-level configuration is proposed for reactive power compensation and simulation and experimental results are presented to confirm the viability of the proposals of this work.